Recurrence Patterns and Predictive Factors in Early-Stage Endometrial Carcinoma: Insights from a Pakistani Cohort Study - Zainab Zubair, Somer Masood, Bahzad Akram Khan, Jawad Ahmed, Syed Asjad Ur Rehman Omer (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Endometrial carcinoma incidence has surged in the Western world over the last two decades and is now increasing in the Eastern regions. Despite diverse treatment approaches, recurrence remains a significant concern, prompting the need to identify prognostic factors to target interventions and improve overall survival rates, thereby alleviating disease burden. Objectives: To identify the frequency of recurrence in its earlier stages and factors influencing it specifically in our part of the world (Pakistan). Methods: A cohort of 250 women who were diagnosed with endometrial carcinoma during 2018 and 2020 underwent treatment (hysterectomy) was studied for up to three years ending till 1 January, 2023following the treatment to identify the rates of recurrence and any predictive factors affecting the illness. The information utilized in this research was acquired from a database of all the patients who visited the Gynae Oncology unit, Lady Willingdon Hospital (King Edward Medical University) Lahore during these years. Results: Out of 250 patients, 13 had a recurrence (5.2%), the various predictive factors identified were FIGO stage 1B (OR 1.89), a score of 3 or more for Charlson comorbidity index (OR 1.88), a histology which is not endometroid and the site of recurrence of the disease. Conclusion: Early-stage endometrial cancer has a low risk of recurrence within 3 years following the initial treatment. Keywords: Endometrial cancer; diagnosis; prognosis; treatment